Integrasi Sistem Presensi Pegawai Berbasis Web dengan Geolokasi dan Swafoto di PT Gresik Migas - Muhammad Romadhon; Deni Sutaji (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manual attendance system using paper at work locations other than offices at PT Gresik Migas creates challenges in the effectiveness and efficiency of employee attendance records. This study implements a web-based attendance system that integrates geolocation and selfie features to improve the accuracy and efficiency of attendance recording. The system was developed using native PHP for backend, jQuery for frontend, MySQL as database, and Leaflet JS for geolocation implementation. Implementation results show the system was successfully implemented in 5 different locations with a 50-meter validation radius and used by 40 employees. This system enables real-time attendance monitoring through an admin dashboard and produces more efficient attendance records compared to the previous manual system.